1998
DOI: 10.1099/0022-1317-79-7-1659
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in SP1 motifs in the upstream regulatory region of human papillomavirus type 18 isolates from cervical cancers increase promoter activity.

Abstract: Evidence of the functional significance of two naturally occurring mutations at nt 40 or 41 in the Sp1 motif in the promoter proximal segment of the upstream regulatory region (URR) of human papillomavirus (HPV) type 18 is presented. In electrophoretic mobility shift assays, Sp1 protein bound more efficiently to the Sp1 mutant motifs than to the prototype ; while in both HeLa and HT3 cells, luciferase activity controlled by the mutant URRs was upregulated 2-and 3-fold, or 4-and 6-fold, in comparison with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
2
21
0
1
Order By: Relevance
“…Consistent with previous findings reporting Sp1 to be a key activator of RNA polymerase II-dependent promoters in HPV (43,52), introduction of a mutation into its binding site caused a significant decrease in LCR promoter activity, which was no longer repressed by IFI16 overexpression. These results indicate that the Sp1 binding site could constitute a target of IFI16.…”
Section: Resultssupporting
confidence: 80%
“…Consistent with previous findings reporting Sp1 to be a key activator of RNA polymerase II-dependent promoters in HPV (43,52), introduction of a mutation into its binding site caused a significant decrease in LCR promoter activity, which was no longer repressed by IFI16 overexpression. These results indicate that the Sp1 binding site could constitute a target of IFI16.…”
Section: Resultssupporting
confidence: 80%
“…However, other studies analyzing nucleotide variability in the LCR, E2, or E6/E7 genes found no correlation between HPV-18 genotypes and lesion grade (31,32). Intratypic variability among HPV-18-positive specimens from North American and Mexican women suggested an association between specific variants and the histopathology findings.…”
Section: Nucleotide Variability and Risk Of Cervical Neoplasiamentioning
confidence: 88%
“…Furthermore, we observed that the HPV-18 prototype sequence was more active than the HPV-16 prototype. It has also been reported that a commonly detected substitution overlapping the Sp-1 binding site at the 3' end of the LCR enhances the transcriptional activity from the P105 HPV-18 main early promoter, since the binding of the Sp-1 protein to this sequence is also increased (31).…”
Section: Nucleotide Variability and Oncogenic Potentialmentioning
confidence: 99%
“…Multiple YY1 binding sites have been identified in the HPV18 upstream regulatory region (URR), of which the promoter-proximal site plays a functional role (22). While the majority of the HPV18 cancer isolates carry mutations or deletions in YY1 binding sites which confer transcriptional activation of the promoter (45)(46)(47)(48), the significance of the promoter proximal YY1 site as a conditional activating site has been recently reported in HeLa cells. When another sequence 130 bp 5' upstream relative to the YY1 site termed the 'switch region' is present in the HPV18 URR, the promoter proximal YY1 site serves as a positive promoter regulatory element.…”
Section: Discussionmentioning
confidence: 99%